2014
DOI: 10.1128/aac.02473-14
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Strategies for Proof-of-Principle Studies of Antibacterial Agents

Abstract: The proof that a new antibacterial agent is not only active in vitro but also effective in vivo under clinically relevant conditions is currently provided (i) by using appropriate nonclinical models of infection and pharmacokinetic-pharmacodynamic (PK-PD) analysis providing evidence of the likelihood of clinical efficacy and (ii) by examining the study drug in exploratory clinical trials, as well as dose and schedule finding during phase II of clinical development. This approach is both time-consuming and cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 98 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…However, PK/PD targets cannot always be derived for all antibacterial agents from studies in experimental animals. The investigational agent MCB3837, a small-molecule prodrug with structural elements of an oxazolidinone and a quinolone being converted to the active substance MCB3681, provides such an example [6]. Alternative strategies thus had to be identified to prove the principle that MCB3681 is antibacterially efficacious in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, PK/PD targets cannot always be derived for all antibacterial agents from studies in experimental animals. The investigational agent MCB3837, a small-molecule prodrug with structural elements of an oxazolidinone and a quinolone being converted to the active substance MCB3681, provides such an example [6]. Alternative strategies thus had to be identified to prove the principle that MCB3681 is antibacterially efficacious in vivo.…”
mentioning
confidence: 99%
“…Alternative strategies thus had to be identified to prove the principle that MCB3681 is antibacterially efficacious in vivo. The evaluation of the effects of an investigational agent on indicator organisms or colonizers of the human resident microflora of healthy volunteers may provide an alternative to traditional proof-of-principle studies [6]. In contrast to the well-established and validated evaluation of the ecology of an antibacterial agent by describing fluctuations of mean viable counts of the human resident microflora within the entire study population during the study period [7][8][9], the intraindividual analysis of its effects on the population densities of indicator organisms or colonizers of the commensal skin, nasal, oropharyngeal and intestinal microflora, paralleled by an evaluation of local drug concentrations as a proof of its in vivo efficacy, has so far not been applied.…”
mentioning
confidence: 99%
“…This apparent discrepancy between pre-clinical and clinical study data and authority-approved indications remains unexplained. The more important it is to scrutinize the relevance of preclinical findings in proof of principle studies at the earliest possible time using alternative strategies [ 51 , 52 ].…”
Section: Non-antimicrobial Activities Of Antibiotics Beyond Structuramentioning
confidence: 99%
“…However, this guideline has been discussed controversially (5), and early responses may not correlate with clinical and microbiological responses at the test-of-cure visit, which is the ultimate goal of antibiotic therapy. However, a recent quantitative analysis of microbiological and/or pharmacodynamic parameters as well as recent clinical trials have confirmed that early evaluation of patients prevented inappropriate or ineffective therapy (6,7). It was demonstrated previously that the more rapid and more pronounced bactericidal in vitro activity of amoxicillin than that of ampicillin is clinically relevant.…”
mentioning
confidence: 95%